2014
DOI: 10.1002/ar.23044
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of the Syrinx of the Chukar Partridge (Galliformes: Alectoris chukar) as a Model for Phonation Research

Abstract: The phonation process of vertebrates is influenced by the material characteristics of the participating structures, ranging from molecular to macroscopic dimensions. Good animal models for phonation research are still lacking. Due to easy availability and relatively simple structure, the syrinx of birds might serve as a good animal model for this purpose. Our aim was therefore to determine structural features of the syrinx and obtain insights into its mucus layer characteristics. Epithelium and glands were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(107 reference statements)
3
9
0
Order By: Relevance
“…For this purpose, we supported the morphological results with conventional mucin histochemistry and immunohistochemistry techniques. Since histochemistry is an excellent method to identify the characterization of glycoconjugates (Schumacher et al, ; Sağsöz and Liman, ; Erdoğan et al, ; Sağsöz et al, ; Erdoğan et al, ), we demonstrated changes in carbohydrate lateral chains of secretions of epithelial cells of the lingual glands. We also evaluated the expression of proteins of MUC1, MUC2, MUC5AC, and MUC6 in epithelial cells of the lingual glands and compared them to the molecular profiles of the mucins.…”
Section: Introductionmentioning
confidence: 74%
“…For this purpose, we supported the morphological results with conventional mucin histochemistry and immunohistochemistry techniques. Since histochemistry is an excellent method to identify the characterization of glycoconjugates (Schumacher et al, ; Sağsöz and Liman, ; Erdoğan et al, ; Sağsöz et al, ; Erdoğan et al, ), we demonstrated changes in carbohydrate lateral chains of secretions of epithelial cells of the lingual glands. We also evaluated the expression of proteins of MUC1, MUC2, MUC5AC, and MUC6 in epithelial cells of the lingual glands and compared them to the molecular profiles of the mucins.…”
Section: Introductionmentioning
confidence: 74%
“…These statements were simulated to that mentioned by (Ragab et al, 2016) in turkey, (Mariana et al, 2013) in rhea, (Khaksar et al, 2012) in turkey, (Onuk et al, 2010) in goose, (Yildiz et al, 2003) in male ostriches. On other hand (Erdogan et al, 2014) in chukar partridge said that the syrinx was formed by the last two tracheal and first eight bronchial cartilages.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional carbohydrate histochemistry, PAS (+) reactions demonstrate the presence of neutral carbohydrates, AF (+) and AB (pH 2.5) (+) reactions indicate the presence of acidic sulfated and carboxylated residues, PAPS (+) reactions point out to the presence of N‐acetyl sialomucins, and Best's carmine and PAS‐diastase reactions show the presence of glycogen (Bancroft & Cook, ; Erdoğan, Sağsöz, & Paulsen, ; Schumacher et al, ). Schumacher et al () reported that, when stained with PAS and AB (pH 1.0 and 2.5), gastric mucins displayed differences between the animal species examined.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoreactivity for MUC1, MUC2, MUC5AC, and MUC6 was evaluated by a semiquantitative scoring method based on the intensity of staining. Four intensity levels (0 for no staining, 1 for weak staining, 2 for moderate staining, and 3 for strong staining) were determine (Erdoğan et al, ; van de Bovenkamp et al, ). Positively stained cells were assessed using blinded preparations and by two independent assessors (H.S.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation